Figur K.H Badawi Hanafi sebagai Pendidik Karakter: Analisis Bibliometrik - Amalia Dwi Nur Hikmah; Eka Nuraeni; Khulaimata Zalfa (Lembaga Yasin AlSys, 2026)
Character education is an important part of shaping learners who are morally upright, responsible, and socially concerned. However, studies on the use of local figures’ biographies as a source of character education remain limited, particularly regarding the figure of K.H. Badawi Hanafi. This study aims to analyze the character education values contained in the biography of K.H. Badawi Hanafi and their relevance to pesantren education. This study used a descriptive qualitative approach with data collection techniques through documentation study, interviews, and scientific literature review. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The results show that the biography of K.H. Badawi Hanafi contains the character values of religiosity, discipline, responsibility, social concern, and integrity, as reflected in his personal life, pesantren educational practices, and socio-religious activities. These values are internalized through role modeling, habituation, and students’ direct experience in everyday life. This study concludes that the biographies of local figures can serve as a contextual source of character education learning that is relevant to community culture. The implications of this study indicate that integrating local figures’ biographies into learning can strengthen students’ character education through role-modeling and real-life experience approaches, particularly in the context of pesantren education.